Functional expression, purification, biochemical and biophysical characterizations, and molecular dynamics simulation of a histidine acid phosphatase from Saccharomyces cerevisiae - Nezhad, Nima Ghahremani; Jamaludin, Siti Zahra; Raja Abd Rahman, Raja Noor Zaliha; Mohd Yahaya, Normi; Oslan, Siti Nurbaya; Mohd Shariff, Fairolniza; Mat Isa, Nurulfiza; Leow, Thean Chor (Springer Science and Business Media, 2024)
A histidine acid phosphatase (HAP) (PhySc) with 99.50% protein sequence similarity with PHO5 from Saccharomyces cerevisiae was expressed functionally with the molecular mass of ∼110 kDa through co-expression along with the set of molecular chaperones dnaK, dnaJ, GroESL. The purified HAP illustrated the optimum activity of 28.75 ± 0.39 U/mg at pH 5.5 and 40 ˚C. The Km and Kcat values towards calcium phytate were 0.608 ± 0.09 mM and 650.89 ± 3.6 s− 1. The half-lives (T1/2) at 55 and 60 ˚C were 2.75 min and 55 s, respectively. The circular dichroism (CD) demonstrated that PhySc includes 30.5, 28.1, 21.3, and 20.1% of random coils, α-Helix, β-Turns, and β-Sheet, respectively. The Tm recorded by CD for PhySc was 56.5 ± 0.34˚C. The molecular docking illustrated that His59 and Asp322 act as catalytic residues in the PhySc. MD simulation showed that PhySc at 40 ˚C has higher structural stability over those of the temperatures 60 and 80 ˚C that support the thermodynamic in vitro investigations. Secondary structure content results obtained from MD simulation indicated that PhySc consists of 34.03, 33.09, 17.5, 12.31, and 3.05% of coil, helix, turn, sheet, and helix310, respectively, which is almost consistent with the experimental results.